Mapping Religious Moderation: Bibliometric Analysis On The Trend And The Future Prespective Of Religious Tolerance - Sita Isna Malyuna; Putri, Rokhmatul Khoiru Amin; Syaifudin, Mokhamad; Niam, Khoirun (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
This article examines the importance of religious moderation within Indonesia's educational framework, especially given its diverse cultural and religious landscape. It addresses the rising challenges of intolerance and extremism that threaten social harmony, highlighting the need for a robust educational approach that promotes tolerance and respect for differences. Through a bibliometric analysis of international publications from the Scopus database, the research identifies key trends in the discourse on religious moderation and its educational implications. Findings indicate a growing interest in incorporating religious moderation into the national curriculum, emphasizing the need for teacher training and the development of inclusive educational materials. The article contributes to academic discourse by underscoring education's role in fostering a tolerant society. It also recommends further research on factors affecting the successful implementation of religious moderation education and advocates for exploring effective teaching methodologies to enhance students' understanding and practice of religious moderation, aiming for a more harmonious educational environment.